Conjugacy of ELF-VLF Emissions at Syowa Station and Husafell (c. Wave-Particle Interactions in the Magnetosphere) (Proceedings of the Second Symposium on Coordinated Observations of the Ionosphere and Magnetosphere in the Polar Regions : Part I) - Natsuo SATO; Masaru AYUKAWA; Hiroshi FUKUNISHI (National Institute of Polar Research, 1980)
Conjugate observations of ELF-VLF emissions, magnetic pulsations and auroras were carried out at Syowa Station in Antarctica and Husafell in Iceland from July 29, 1977 to September 18,1977. Husafell is located at a distance of about 50 km from the conjugate point of Syowa Station. Conjugacies of ELF-VLF emissions depend on emission types, such as polar chorus, quasiperiodic emissions, burst of discrete emissions and auroral hiss. Polar chorus and quasi-periodic emissions are observed simultaneously at the conjugate-pair stations. This suggests that the emissions are generated near the equatorial region in the outer magnetosphere and propagate to the both hemispheres along the field lines of force. Conjugacy of bursts of discrete emissions and auroral hiss is generally low. The emission intensity of auroral hiss is much stronger at Syowa Station (winter hemisphere) than at Husafell (summer hemisphere). Just the opposite tendency is observed for bursts of discrete emissions. The low conjugacy of these emissions may depend on the differences in geophysical conditions, such as the magnetic field, magnetic dip angle and the plasma density and also it depends on properties of the generation region of the emissions.